Mia Mayhem stops time! - West, Kara (New York : Little Simon, 2019)
When Mia first learned she had superpowers, there was one ability that always came rather naturally: freezing time and people! So, when she finally learns the secret to controlling it, she's excited to put her new skills to the test. But when she ends up accidentally freezing the entire town, will she find a way to make the clock start ticking again?
3.1
K-3
580L
Keywords: Superheroes -- Juvenile fiction; Time -- Juvenile fiction; African Americans -- Juvenile fiction; Superheroes -- Fiction; Time -- Fiction; African Americans -- Fiction; Superhero fiction